BRAND EQUITY, INOVASI PRODUK, DAN KEPUTUSAN PEMBELIAN: PERAN MEDIASI LOYALITAS MEREK DALAM KONTEKS PASAR HALAL - Syafruddin Syafruddin; Hikmah Hikmah; Andi Batary Citta (Journal Economic Management and Business, 2026)
This study analyses the influence of brand equity and product innovation on purchase decisions through brand loyalty among consumers of Halal Network International (HNI) in South Sulawesi. The research applied a quantitative explanatory approach using SEM-PLS analysis on data collected from 160 HNI consumers. The findings reveal that brand equity significantly enhances brand loyalty, although it does not directly affect purchase decisions. Meanwhile, product innovation has a significant positive effect on both brand loyalty and purchase decisions. Brand loyalty was identified as the strongest determinant of purchase decisions. In addition, brand loyalty fully mediates the relationship between brand equity and purchase decisions, while partially mediating the influence of product innovation. These results suggest that consumer purchasing behaviour in the halal market is driven more by trust and emotional attachment to the brand than by brand strength alone, offering both theoretical and practical contributions to marketing strategy development.